"Thought provoking", "interactive", and "more like a peer talk": Testing the deliberative interview style in Germany - Astrid Berner-Rodoreda; Till Bärnighausen; Nir Eyal; Malabika Sarker; Puspita Hossain; Melkizedeck Leshabari; Emmy Metta; Elia Mmbaga; Daniel Wikler; Shannon A. McMahon (Elsevier, 2021)
Proponents of the newly-developed "deliberative interview" argue that examining complex issues requires more dynamic and engaging interview exchanges. Unlike traditional qualitative interviews, deliberative interviewing champions opinion sharing, active debates and similar speaking times by both sides throughout the interview. Drawing on 20 interviews with health experts in Germany, we examined the process and outcome of deliberative versus conventional interviews on the topic of informed consent. The deliberative interview expedited clarity on the issue, led to more nuanced discussion and generated more knowledge overall, but was challenging because it broke the mold for traditional interviewing. Alignment in terms of gender, age, personality and professional background facilitated rapport, regardless of interview style. To manage expectations, we recommend a thorough, perhaps video-based explanation of the deliberative style prior to the interview. Deliberative interviews can bolster knowledge generation for complex issues and can be applied in public health and beyond.